Amplification of coupled hot-dry extremes over eastern monsoon China - Zhang, X.; Gu, X.; Slater, L. J.; Dembélé, Moctar; Tosunoğlu, F.; Guan, Y.; Liu, J.; Kong, D.; Xie, F.; Tang, X. (American Geophysical Union, 2023)
High air temperatures and low atmospheric humidity can result in severe disasters such as flash droughts in regions characterized by high humidity (monsoon regions). However, it remains unclear whether responses of hot extremes to warming temperature are amplified on dry days as well as the response of dry extremes on hot days. Here, taking eastern monsoon China (EMC) as a typical monsoon region, we find a faster increase in air temperature on drier summer days, and a faster decrease in atmospheric humidity on hotter days, indicating “hotter days get drier” and “drier days get hotter” (i.e., coupling hotter and drier extremes), especially in southern EMC. The southern EMC is also a hotspot where the coupling hot-dry extremes has become significantly stronger during the past six decades. The stronger hot-dry coupling in southern EMC is associated with anomalies in large-scale circulations, such as reduced total cloud cover, abnormal anticyclones in the upper atmosphere, intense descending motion, and strong moisture divergence over this region. Land-atmosphere feedback enhance the hot-dry coupling in southern EMC by increasing land surface dryness (seen as a decrease in the evaporation fraction). The decreasing evaporation fraction is associated with drying surface soil moisture, controlled by decreases in pre-summer 1-m soil moisture and summer-mean precipitation. Given hot extremes are projected to increase and atmospheric humidity is predicted to decrease in the future, it is very likely that increasing hot-dry days and associated disasters will be witnessed in monsoon regions, which should be mitigated against by adopting adaptive measures.